ERAP1: a potential therapeutic target for a myriad of diseases. (2nd June 2020) - Reeves, Emma; Islam, Yasmin; James, Edward
ABSTRACT: Introduction : Endoplasmic Reticulum Aminopeptidase 1 (ERAP1) is a key regulator of the peptide repertoire displayed by Major Histocompatibility Complex I (MHC I) to circulating CD8 + T cells and NK cells. Studies have highlighted the essential requirement for the generation of stable peptide MHC I in regulating both innate and adaptive immune responses in health and disease. Areas covered : We review the role of ERAP1 in peptide trimming of N-terminally extended precursors that enter the ER, before loading on to MHC I, and the consequence of loss or downregulation of this activity. Polymorphisms in ERAP1 form multiple combinations (allotypes) within the population, and we discuss the contribution of this ERAP1 variation, and expression, on disease pathogenesis, including the resulting effect on both innate and adaptive immunity. We consider the current efforts to design inhibitors based on approaches using rational design and small molecule screening, and the potential effect of pharmacological modulation on the treatment of autoimmunity and cancer. Expert opinion : ERAP1 is fundamental for the regulation of immune responses, through generation of the presented peptide repertoire at the cell surface. Modulation of ERAP1 function, through design of inhibitors, may serve as a vital tool for changing immune responses in disease.